Pattern of Esbls in Uro-Pathogens Obtained from a Nigerian Tertiary Hospital (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Multidrug resistance remains a challenge in the treatment of Urinary Tract Infections (UTI) in Nigeria, a key factor being the occurrence of ESBL producers. Earlier reports have emphasized the occurrence of major ESBLs, little is known about the minor subtypes' occurrence in this regard.Objective: This study sought to evaluate the occurrence of major and minor ESβL producers among a cohort of uropathogens collected from a Nigerian Teaching Hospital using molecular techniques.Material and Methods: Cultures from 1000 UTI positive urine specimens were collected from the hospital laboratory between May 2015 and December 2017. All samples were subjected to standard isolation culturing techniques and identified. They were further tested for susceptibility to 8 antibiotics. Of these, gram-negative isolates with presumptive ESBL production were evaluated for confirmatory ESBL production using Chromogenic ESBL agar (Oxoid) and Agar Dilution tests. One hundred and twenty-five of them were evaluated for the presence of six ESBL genes (TEM, SHV, CTX-M 15, PER, GES, VEB) using Multiplex PCR/Agarose Gel Electrophoresis.Results: The results revealed that 40 out of 97 (41%) detected ESBL genes were of the ESBL minor category (VEB, PER, and GES). These ESBL producers were also observed to be resistant to at least five of the 8 antibiotics tested.Conclusion: More attention should be paid to the emergence minor ESBL producers among uropathogens in this environment as they represent a potential underlying influence on the observed treatment failure in the treatment of UTI.